Holding the man [videorecording (DVD)] - Corr, Ryan, 1989-; Stott, Craig; Fox, Kerry; Kin, Camilla Ah; Pearce, Guy, 1967-; LaPaglia, Anthony; Rush, Geoffrey, 1951-; Conigrave, Timothy, 1959-1994 (Strand Releasing, 2015)
The love story of two high school boys, one the hunky captain of the football team and the other sensitive drama student. After a sweet courtship, the two fall madly in love and traverse an enduring relationship over fifteen years.